Low expression of APAF-1XL in acute myeloid leukemia may be associated with the failure of remission induction therapy - Benites,B.D. (2008)
Apoptotic protease activating factor 1 (APAF-1) has a critical role in the regulation of apoptosis. In the present study, the mRNA expression analysis of different APAF-1 transcripts (APAF-1S, APAF-1LC, APAF-1LN, and APAF-1XL) was analyzed in bone marrow samples from 37 patients with acute myeloid leukemia (newly diagnosed, with no previous treatment). APAF-1XL and APAF-1LN transcripts (with and without an extra WD-40 repeat region, respectively) were detected in all samples, although the major form expressed was APAF-1XL in 65% of the samples (group 1), while 35% of the samples expressed primarily APAF-1LN (group 2). Only 46% of the patients presented complete remission in response to remission induction therapy (represented by less than 5% marrow blasts and hematological recovery), all but 2 cases being from group 1, 21.6% did not attain complete remission (only 1 case from group 1), and 32.4% of the patients died early. Lower expression of APAF-1XL (APAF-1XL/APAF-1LN ratio <1.2) was associated with a poor response to therapy (P = 0.0005, Fisher exact test). Both groups showed similar characteristics regarding white blood cell counts, cytogenetic data or presence of gene rearrangements associated with good prognosis as AML1-ETO, CBFB-MYH11 and PML/RARA. Since it has been shown that only the isoforms with the extra WD-40 repeat region activate procaspase-9, we suggest that low procaspase-9 activation may also be involved in the deregulation of apoptosis and chemotherapy resistance in acute myeloid leukemia.